Study on Role of a Raja Rao In Indian English Literature: Exploring the Impact of Raja Rao on Indian English Literature and Postcolonial Theory (Journal of Advances and Scholarly Researches in Allied Education, 2013)
After Rao, Indian writings in English started employingmagical realism, bagginess, nonlinear narrative and hybrid language to sustainthemes seen as microcosms of India and supposedly reflecting Indian conditions.He contrasts this with the works of earlier writers such as Narayan where theuse of English is pure, but the deciphering of meaning needs culturalfamiliarity. He also feels that Indianness is a theme constructed only in IWEand does not articulate itself in the vernacular literatures. He further adds"the post-colonial novel becomes a trope for an ideal hybridity by whichthe West celebrates not so much Indianness , whatever that infinitely complexthing is, but its own historical quest, its reinterpretation of itself". Some of these arguments form an integral part of what iscalled postcolonial theory. The very categorisation of IWE – as IWE or underpost-colonial literature – is seen by some as limiting. Amitav Ghosh made hisviews on this very clear by refusing to accept the Eurasian CommonwealthWriters Prize for his book The Glass Palace in 2001 and withdrawing it from thesubsequent stage. The renowned writer V. S. Naipaul, a third generationIndian from Trinidad and Tobago and a Nobel Prize laureate, is a person whobelongs to the world and usually not classified under IWE. Naipaul evokes ideasof homeland, rootlessness and his own personal feelings towards India in manyof his books. Jhumpa Lahiri, a Pulitzer Prize winner from the U.S., is a writeruncomfortable under the label of IWE. Recent writers in India such as ArundhatiRoy and David Davidar show a direction towards contextuality and rootedness intheir works. Arundhati Roy, a trained architect and the 1997 Booker prizewinner for her The God of Small Things, calls herself a "home grown"writer.